Development of the Brand Authenticity Scale for Professional Sport Teams - Seunghwan Lee (Korea Institute of Sport Science, 2022)
PURPOSE This study aimed to identify the underlying dimensions of brand (professional sport team) authenticity and to develop a valid, reliable scale to measure these dimensions. METHODS A pool of 67 potential items was drawn through a literature review, content analysis, qualitative research (n=43), and an expert evaluation. The identified items were subjected to exploratory factor analysis (n=248) and confirmatory factor analysis (n=285). In addition, multiple regressions were conducted to examine the criterion validity of the scale. RESULTS The results showed that the brand authenticity scale for professional sport teams consists of 42 items representing 8 dimensions: continuity, originality, quality commitment, heritage, symbolism, credibility, stakeholder-related integrity, and consumer-related integrity. The study has proven evidences of internal consistency and convergent, discriminant, and criterion validity of the scale. CONCLUSIONS The findings suggest that the scale developed in this study offers a vital foundation to understand the structure of brand authenticity in the context of sport fans and its impact on sport consumer behavior.